Recognition and manipulation of branched DNA by the RusA Holliday junction resolvase of Escherichia coli. - Chan, S N (1998)
Homologous recombination is a fundamental cellular process that shapes and reshapes the genomes of all organisms and promotes repair of damaged DNA. A key step in this process is the resolution of Holliday junctions formed by homologous DNA pairing and strand exchange. In Escherichia coli , a Holliday junction is processed into recombinant products by the concerted activities of the RuvA and RuvB proteins, which together drive branch migration, and RuvC endonuclease, which resolves the structure. In the absence of RuvABC, recombination can be promoted by increasing the expression of the RusA endonuclease, a Holliday junction resolvase encoded by a cryptic prophage gene. Here, we describe the DNA binding properties of RusA. We found that RusA was highly selective for branched molecules and formed complexes with these structures even in the presence of a large excess of linear duplex DNA. However, it does bind weakly to linear duplex DNA. Under conditions where there was no detectable binding to duplex DNA, RusA formed a highly structured complex with a synthetic Holliday junction that was remarkably stable and insensitive to divalent metal ions. The duplex arms were found to adopt a specific alignment within this complex that approximated to a tetrahedral conformation of the junction.